One-Pot Synthesis of Dialkyl 2-[(2,5-Dioxo-1-pyrrolidinyl)- oxy]-2-butenedioates from Acetylenic Esters and n-Hydroxysuccinimide - REZA KAZEMIZADEH, ALI; RAMAZANI AND BIJAN GANJEIE, ALI (Asian Journal of Chemistry, 2010)
A one-pot synthesis of electron-poor O-vinyl pyrrolidine in fairly high yields by the reaction of N-hydroxysuccinimide and dialkyl acetylenedicarboxylates in water-acetone media is reported. The structures of these compounds were confirmed by IR, 1H and 13C NMR spectroscopy. The NMR spectra indicated that E- and Z-isomers of the products are formed.